ARCHAEOLOGICAL EVIDENCE IN CALLE REAL AVENUE, VILCASHUAMÁN-AYACUCHO - Cavero Palomino, Yuri I. (2014)
In this article the archaeological evidence consisting of two segments of channels and 2 sections of cobbled remains of roads, found during work to replace the pavement layer and the water pipes and drainage made in the first block of exposed Av. Camino Real in the city of Vilcashuamán, which during Inca times was the capital of the administrative center of the same name.